2019
DOI: 10.1177/1363461519847299
|View full text |Cite
|
Sign up to set email alerts
|

Identification with ancestral culture is associated with fewer internalizing problems among older Naskapi adolescents

Abstract: The manifestations of externalizing and internalizing behaviors among minority adolescents might best be understood by examining their relation to culturally specific factors, such as cultural identity, as well as to factors that seem to be relevant across cultures, such as age and gender. In this study, we examined the roles of age and gender in moderating the relation between self-reported cultural identity and externalizing and internalizing problems and the interaction between Indigenous and Mainstream cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In keeping with Ed's conceptualizations of the complexity of development, we have noted that the impact of culturally mismatched schools can be nuanced. While we, like others, have found that identification with one's own ancestral culture of heritage contributes to the various aspects of wellbeing among North American Indigenous youth (Blacklock et al, 2020; Flanagan et al, 2011; for a review, see Burack et al, 2014), its beneficial influences might be attenuated by their incompatibility, or mismatch, with the majority culture – especially in institutions such as schools (Fryberg, Troop-Gordon, et al, 2013). Accordingly, as Ed advocated so passionately, schools need to be designed to enhance students’ success; in this case, we and our colleagues argue that the identification and modification of cultural mismatches in the school context are first steps in promoting positive school experiences that lead to educational success and retention among Indigenous students, regardless of their level of identification with the ancestral or majority culture.…”
Section: Ed's Influence On Our Group's Work In Developmental Psychopathology: Examples From Research With Persons With Asd and Indigenousmentioning
confidence: 60%
“…In keeping with Ed's conceptualizations of the complexity of development, we have noted that the impact of culturally mismatched schools can be nuanced. While we, like others, have found that identification with one's own ancestral culture of heritage contributes to the various aspects of wellbeing among North American Indigenous youth (Blacklock et al, 2020; Flanagan et al, 2011; for a review, see Burack et al, 2014), its beneficial influences might be attenuated by their incompatibility, or mismatch, with the majority culture – especially in institutions such as schools (Fryberg, Troop-Gordon, et al, 2013). Accordingly, as Ed advocated so passionately, schools need to be designed to enhance students’ success; in this case, we and our colleagues argue that the identification and modification of cultural mismatches in the school context are first steps in promoting positive school experiences that lead to educational success and retention among Indigenous students, regardless of their level of identification with the ancestral or majority culture.…”
Section: Ed's Influence On Our Group's Work In Developmental Psychopathology: Examples From Research With Persons With Asd and Indigenousmentioning
confidence: 60%
“…Elsewhere, Snowshoe (2016) reported that cultural connectedness (i.e., affiliative identity, traditions, and spirituality) positively affected First Nations young people's mental health. The benefits of cultural connectedness were found in another study with First Nations young people in which indigenous cultural identity was negatively correlated with internalizing problems (i.e., depression, anxiety, and fearfulness) (Blacklock et al, 2020).…”
Section: Differentiating Historical Trauma From Contemporarymentioning
confidence: 89%
“…In this sample, a number of studies emphasized the value of enculturation, the ways in which an Indigenous person's having ties to their culture offered protection against present-day effects of past colonization (Blacklock et al, 2020;Cloud Ramirez & Hammack, 2014). Ungar (2006), for example, referred to the importance to Indigenous people of being in touch with a collective history of trauma as a means of connecting to the land, family roles and relationships, and traditional ways of health and healing.…”
Section: Differentiating Historical Trauma From Contemporarymentioning
confidence: 99%
“…They range from service recipient case studies (Kopua et al., 2020) to large survey samples that were designed to generalize to a national population (Fuller-Thomson et al.). They focus by design on younger student-aged populations (Blacklock et al., 2020; Hop Wo et al.) or vocation-specific respondents (such as clinicians [Dagsvold et al., 2020] or firefighters [Stanley et al., 2020]).…”
Section: Capturing Indigeneity In Indigenous Mental Health Researchmentioning
confidence: 99%
“…They range from service recipient case studies (Kopua et al, 2020) to large survey samples that were designed to generalize to a national population (Fuller-Thomson et al). They focus by design on younger student-aged populations (Blacklock et al, 2020;Hop Wo et al) or vocationspecific respondents (such as clinicians [Dagsvold et al, 2020] or firefighters [Stanley et al, 2020]). They include community-based participants whose responses presumably reflect contemporary tribal life (e.g., Naskapi school children [Blacklock et al], Southeastern tribal nations in the USA [McKinley et al, 2020], or Swampy Cree reserves in Canada [Isaak et al, 2020]).…”
Section: Capturing Indigeneity In Indigenous Mental Health Researchmentioning
confidence: 99%